1997
DOI: 10.1006/dbio.1996.8463
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Embryonic Intracellular Ca2+Signaling byWnt-5A

Abstract: Wnt genes encode secreted proteins which are implicated in receptor-mediated cell-cell signaling events important in embryogenesis, but the second messenger systems modulated by Wnts have not been identified. We report that ectopic expression of Xwnt-5A in zebrafish embryos enhances the frequency of intracellular Ca2+ transients in the enveloping layer of the blastodisc, whereas Xwnt-8 does not. These transients are independent of extracellular Ca2+. Consistent with the observed Ca2+ transients playing a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
294
0
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(321 citation statements)
references
References 28 publications
14
294
0
6
Order By: Relevance
“…In addition to signaling via ROR2, it is likely that WNT5A has further functions because Wnt5a −/− mice have a more severe digit phenotype than Ror2 −/− mice (23). WNT5A is known to signal via Frizzled receptors to noncanonical pathways including the WNT/calcium pathway (26), which can also inhibit the β-catenin pathway (27). Thus it is conceivable that the truncated ROR2 protein might act as a scavenger for WNT5A, thus inhibiting WNT5A signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to signaling via ROR2, it is likely that WNT5A has further functions because Wnt5a −/− mice have a more severe digit phenotype than Ror2 −/− mice (23). WNT5A is known to signal via Frizzled receptors to noncanonical pathways including the WNT/calcium pathway (26), which can also inhibit the β-catenin pathway (27). Thus it is conceivable that the truncated ROR2 protein might act as a scavenger for WNT5A, thus inhibiting WNT5A signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, integrindependent signaling pathways are involved in the activation of phosphatidyl inositol 3-kinase (PI3-kinase) through integrin-linked kinase (ILK) (Chen et al, 1996;King et al, 1997). In addition, recent studies have demonstrated that the Wnt signal also activates the phosphatidyl inositol signaling pathway (Slusarski et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequencing projects have revealed that a large number of Wnt genes exist, including 7 Wnt genes in Drosophila and at least 19 Wnt genes in humans. 1 Wnt proteins function as growth factors and morphogens modulating cell growth and specifying cell fate.…”
mentioning
confidence: 99%
“…Embryonic studies in Xenopus and Zebrafish indicate that overexpression of Wnt5a results in an increased release of intracellular calcium (19). Wnt5a overexpression can also lead to increased activation of classical protein kinase C and calmodulin-dependent protein kinase II (CamKII) (20,21), two calcium-responsive serine threonine kinases.…”
mentioning
confidence: 99%